Characteristics and phylogenetic analysis of the complete mitochondrial genome of Microstomus achne. Issue 2 (1st February 2023) - Chae, Jun Young; Kim, JinHo; Kang, Tae-Wook; Kim, Jinkoo; Lee, Hyung-Ho; Kim, Moo-Sang
Abstract: Microstomus achne (Jordan and Starks, 1904) is an economically valuable flatfish belonging to the family Pleuronectidae and the only flatfish that inhabits Korea. Here, we report on the complete mitochondrial genome of M. achne and the phylogenetic relationship between close species. The mitogenome is 16, 971 bp long and encodes 13 protein-coding genes (PCGs), 22 transfer RNAs, and two ribosomal RNAs. The phylogenetic analysis showed that M. achne clustered with Glyptocephalus stelleri, which supports the conclusion that M. achne belongs to the family Pleuronectidae. The results of this study provide a better understanding of M. achne .